Police Corruption and Crime Reporting: A Study of Bribery in Wukari Local Government Area, Taraba State, Nigeria - Sabastine, Ediba; Isaiah, Jude Ure; Daude, Gbana Nkpujire-ekah (Darul Yasin Al Sys, 2025)
Police bribery remains a pervasive issue in Nigeria, significantly undermining public trust in law enforcement, particularly in semi-urban areas such as Wukari Local Government Area of Taraba State. Many citizens perceive that police officers routinely demand bribes before acting on crime reports and that justice is more readily available to individuals with financial means. These perceptions contribute to widespread reluctance to report crimes, especially among the poor and marginalized, leading to a deterioration of police-community relations. This study investigates the extent to which police bribery influences crime reporting behavior in Wukari. A descriptive, cross-sectional survey design was adopted, with a sample size of 400 respondents selected from a population of 374,800 using the Taro Yamane formula. Data were collected via questionnaires distributed through random sampling, yielding 350 valid responses. Descriptive statistics, including frequencies, percentages, means, and standard deviations, were used for analysis. The findings indicate that crime reporting is generally low, with police bribery identified as a significant deterrent. Respondents frequently cited fear of being asked for bribes or being ignored due to inability to pay as reasons for non-engagement with law enforcement. The study concludes that police bribery not only discourages crime reporting but also erodes the legitimacy and credibility of the Nigeria Police Force. It recommends the strict enforcement of anti-corruption policies, the promotion of community-oriented policing strategies, and the establishment of independent and anonymous crime reporting mechanisms to restore public confidence in law enforcement institutions.